Pengembangan Kecerdasan Spiritual Pada Anak Usia Dini Melalui Pembiasaan Kegiatan Keagamaan Di TK Sokanegara - Miftakhul Janah, Sinta (Jambura Early Childhood Education Journal, 2023)
Parents think that a child's success is only seen from his intellectual success, and it is even embedded in society in general that a child will be said to be qualified if the child has good exact scores, and vice versa. Whereas in fact intelligence is not only limited to intellectual intelligence, but there are other intelligences that can be opportunities to be developed, for example spiritual intelligence.The purpose of this study was to analyze the development of spiritual intelligence in early childhood through religious habituation activities in Kindergarten Kelurahan Sokanegara. This study used a qualitative method with interview, observation and documentation collection techniques and analyzed by data analysis of the Miles and Huberman models. In this study resulted that through religious activities can develop the spiritual intelligence of early childhood challenged with the occurrence of changes (in good terms) or the development of spiritual intelligence is characterized by the tendency of children to be more calm when carrying out religious activities (the habit of praying dhuha in congregation), and also the reading of prayers becomes better because it is supported by the habit of memorizing letters, daily prayers and hadiths.